Small colony variants of Burkholderia pseudomallei: alteration of the virulence factors - Vanitha Mariappan; Muttiah Barathan; Ahmad Khusairy Zulpa; Jamuna Vadivelu; Kumutha Malar Vellasamy (Journal of Taibah University for Science, 2023)
Burkholderia pseudomallei produce small colony variants (SCVs) that can persist in harsh conditions. This study aimed to compare SCV with B. pseudomallei wild-type (WT) in the ability to adhere, invade, survive and produce biofilm. Additionally, proteins responsible for pathogenicity were determined through two-dimensional gel electrophoresis (2-DE) and liquid-chromatography mass-spectrometry (LC-MS). Whole bacterial proteins analysed using 2-DE demonstrated 252 and 323 protein spots in WT and SCV, respectively, with 37 distinctive proteins identified in the SCV. Several isoform proteins (dnaK, groEL1, gapA and tuf), upregulated in SCV, may function as moonlighting proteins. Quantitative proteomic analysis using LC-MS revealed 57 and 99 distinctive proteins in the WT and SCV, respectively. Many distinct proteins communicated by B. pseudomallei SCV were involved in the metabolic pathways and may play a role in the alteration of virulence factors. Thus, the alteration of proteins in SCVs may be an approach of B. pseudomallei to enhance pathogenesis.